Analisis Pelayanan Penerbitan Surat Izin Mendirikan Bangunan (IMB) di Dinas Penanaman Modal Pelayanan Terpadu Satu Pintu Dan Tenaga Kerja Kota Sungai Penuh - Fandi Esa Primadi; Rudi Febrianmansyah; Jafrinur Jafrinur (Jurnal Administrasi dan Kebijakan Publik, 2022)
This research was conducted at the One Stop Integrated Service and Manpower Investment Service (DPMPTSPTK) Sungai Penuh City. This research was conducted to find out how the implementation of IMB (building permit) granting in various forms of IMB and to find out the service inhibiting factors in the issuance of IMB in Sungai Penuh City. This research was conducted using a quantitative descriptive method combined with a qualitative descriptive method. The survey population of this study was the entire community of applicants for IMB at the office of DPMPTSPTK Sungai Penuh City in 2019, while the sample from this study was part of the population. The sampling technique in this study used the Slovin formula with a significance level of 0.05. From the study on the implementation of IMB granting, it was found two factors inhibited the process, namely the time factor and the completion factor. The time factor is the worst factor with the lowest average score (2.76) of the six service standards. In general, the delay in the IMB issuance process is due to the officer concerned rarely being in the area or outside the area. While the cost factor has the second lowest average score (2.87) of the six service standards. It was found that almost all requests/respondents who complained about the tariffs or levies imposed were quite high.